Néstor Sánchez y Osvaldo Baigorria: una amistad posible - Julia Musitano (Cuadernos LIRICO)
For Osvaldo Baigorria, it was not free to write the biography of Néstor Sánchez. Backwards and forwards, Baigorria's literature underwent a process of transformation. Backwards: Baigorria revisits old categories with which he worked to "befriend" Sánchez and be able to write about him. Forwards: everything that Baigorria writes after the biography (Postales de contracultura and Indiada) is crossed by the figure of Sánchez. That is why I am interested in tracing the features that made a friendship between Sánchez and Baigorria possible, and the reasons why one's literature is contaminated by the literature of the other when life gets in the way. I propose a reading of the biography in a loving key in accordance with the way I postulate the link between biographer and biographer.